Central Bank’s Announcements Effects on the Romanian Market - Alina ZAHARIA-ROTARU (Communications of International Proceedings, 2024)
This study examines the effects of domestic monetary policy rate change announcements made by the central bank on the stock market returns and volatility in Romania. By utilizing event study methodologies under the Market Model, the analysis captures stock price reactions to these announcements in the 2003-2023 period, catching multiple phases of the financial and business cycles. The analysed period also captures multiple important events that marked the Romanian economy, including the 2008 crisis and the COVID-19 pandemic, therefore offering a robust understanding of the market participants reactions to the central bank’s interventions, decisions and tools. Furthermore, this research enhances the application of event study techniques in emerging markets. Overall, the analysis reveals that Romania’s market reactions to monetary policy announcements often skew negative, reflecting cautious sentiment and scepticism about the implemented monetary policy measures, aligning with the findings of the economic literature focused on developed economies. However, the overall response magnitude in Romania is modest, indicating that positive reactions occur often. These findings suggest that the market’s conservative behaviour stems from precautionary measures. As Romania integrates further into the global financial system, these insights are vital for policymakers and investors, highlighting the need for continuous monitoring and adaptation in monetary policy to better navigate the complex economic landscape. By analysing a country located in the CEE region, this study adds to the economic research concerning the impact of monetary policy decisions, which has predominantly focused on the developed economies and regions until now, remaining scarce on the developing ones.
Keywords: event study methods; monetary policy announcements; CEE economies; markets responses